Chapter 10 Comparing culturally embedded frames of judicial dispassion - Wettergren, Åsa (Research Handbooks in Legal Theory series, 2021)
This illuminating Research Handbook analyses the role that emotions play and ought to play in legal reasoning and practice, rejecting the simplistic distinction between reason and emotion.